Audit Energi Listrik pada Bangunan Gedung SMKN 3 Kuningan - Sofia Nurul Fajri; Nundang Busaeri; Imam Taufiqurrahman (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2024)
This research discusses Energy Audit at SMKN 3 Kuningan with the objective of evaluating the energy consumption intensity (IKE) in the buildings of SMKN 3 Kuningan. The methodology applied in this research involves measuring energy consumption through an energy audit and evaluating the measurement results based on IKE. The results obtained from data processing show that the total electrical energy consumption of the SMKN 3 Kuningan buildings is 112,613.11 kWh/year. Electrical energy consumption in air-conditioned rooms accounts for 80% of the total energy consumption, with electrical energy usage of 7,473 kWh/month, while non-air-conditioned rooms account for 20% of the total energy consumption, with an energy usage of 1,854 kWh/month. The calculated IKE value for air-conditioned rooms in SMKN 3 Kuningan buildings is 1.88 kWh/m²/month. Therefore, the air-conditioned rooms of SMKN 3 Kuningan buildings fall into the very efficient category as the IKE value is < 8.5 kWh/m²/month. The calculated IKE value for the non-air-conditioned rooms in SMKN 3 Kuningan buildings is 0.25 kWh/m²/month. Thus, the non-air-conditioned rooms of SMKN 3 Kuningan buildings fall into the very efficient category as the IKE value is < 3.4 kWh/m²/month. Both air-conditioned and non-air-conditioned rooms in the SMKN 3 Kuningan buildings meet the criteria for very efficient energy consumption intensity. Nevertheless, further research on energy saving opportunities can still be conducted to minimize electricity consumption costs at SMKN 3 Kuningan.